The (dis)interest of the CJEU in the transfer of the centre of main interests in insolvency proceedings in times of Brexit. Commentary to CJEU Ruling of 24th March 2022, Galapagos BidCo, C-723/20 - Mariscal González, Ada Lucía (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
the purpose of this paper is to delve into the interpretative criteria on Article 3(1) of the Regulation on Insolvency Proceedings contained in the ruling of the CJEU of 24th of March 2022, Galapagos BidCo, C-723/20, which aims to clarify which court has international jurisdiction to open main insolvency proceedings, when there is a prior application for the opening of insolvency proceedings before a court of another Member State and the latter has not declined or assumed jurisdiction. For this purpose, the referring court asks the CJEU for criteria in the Regulation in order to determine the location of the debtor’s centre of main interests, provided that there are several relocations within a short period of time, which may be understood as a search by the debtor for a forum of convenience to the detriment of its creditors. Although the CJEU does not offer criteria to clarify the location, it does point out that the application for main insolvency proceedings before a court of one Member State excludes, by virtue of the principle of perpetuatio fori, the jurisdiction of the courts of another Member State to open similar proceedings with the same object.
Keywords: European Insolvency Regulation; cross-border insolvency; international jurisdiction; opening of the main insolvency proceedings; transfer of the centre of main interests